1260 Comparison of the Intramedullary Nail and Dynamic Hip Screw in the Management of Subtrochanteric Femoral Fractures. (12th October 2021) - Arshad, Z; Thahir, A; Rawal, J; Hull, P; Carrothers, A; Krkovic, M; Chou, D T S
Abstract: Aim: Subtrochanteric femoral fractures are said to occur in the 5cm of bone immediately distal to the lesser trochanter. This study aims to compare peri-operative outcome measures in patients with subtrochanteric fractures treated with either an IMN, or an alternative construct, the dynamic hip screw (DHS). Method: A retrospective review of all subtrochanteric fractures presenting to our institution between October 2014 and May 2019 was performed. All patients were classified into two treatment groups, IMN or DHS. These groups were compared on outcome measures including radiation dose area product (DAP), length of hospital stay, estimated blood loss, mortality, and re-operation/complication rate. Results: A total of 86 patients presented to our institution with a subtrochanteric femoral fracture during the study time period. Of these, 74 (86%) received an IMN and the remaining 12 (14%) received a DHS. The only comparative outcome measures showing a statistically significant difference between the two groups were radiation DAP and blood loss., both of which were significantly lower in the DHS group. All other comparative outcome measures failed to reach statistical significance. Conclusions: Although current United Kingdom national guidelines advise all subtrochanteric femoral fractures should be treated with an IMN, the outcome measures used in this study suggest that the DHS, which also has a reduced implant cost compared to an IMN, may be the better option in some cases. There may not be one optimal implant for all subtrochanteric fractures. Recent biomechanical research suggests that the DHS is able to provide adequate fixation in more stable fracture subtypes, whereas an IMN may be required for unstable subtrochanteric fractures.